2023
DOI: 10.14710/reaktor.22.3.92-101
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid fermentation of banana peel using Lactobacillus plantarum : Effect of substrate concentration, inoculum concentration, and various nitrogen sources

Abstract: Semeru Banana peel is an organic waste that is exclusively utilized as animal feed and does not harm the environment. The primary component of banana peels is carbohydrates, which can be used as a substrate during the fermentation process to produce lactic acid. The fermentation of banana peel flour with Lactobacillus plantarum strain FNCC 0020 was the main focus of this investigation. Variations in the concentrations of the substrate and inoculum as well as the impact of the type of nitrogen on lactic acid co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…In the treatment P0 (0%) acetic acid content of vinegar 0.6 %, P1 (10%) acetic acid content 6%, P2 (20%) acetic acid content 4.8%, P3 (30%) acetic acid content 4.2%, and P4 (40%) acetic acid content 3%. In line with research conducted by Abdullah et al (2023) semeru banana peel is organic waste that is only used as animal feed and does not harm the environment. The main component of banana peel is carbohydrates that can be used as substrates during the fermentation process to produce lactic acid.…”
Section: Resultssupporting
confidence: 56%
“…In the treatment P0 (0%) acetic acid content of vinegar 0.6 %, P1 (10%) acetic acid content 6%, P2 (20%) acetic acid content 4.8%, P3 (30%) acetic acid content 4.2%, and P4 (40%) acetic acid content 3%. In line with research conducted by Abdullah et al (2023) semeru banana peel is organic waste that is only used as animal feed and does not harm the environment. The main component of banana peel is carbohydrates that can be used as substrates during the fermentation process to produce lactic acid.…”
Section: Resultssupporting
confidence: 56%
“…The LcS strain, a lactic acid bacterium, functions optimally in anaerobic to microaerophilic conditions, leading to the conversion of organic macromolecules into acetate, ethanol, lactic acid, methane, and volatile fatty acids (Lin et al, 2018). Theoretically, a low concentration of inoculum is introduced, slowing down fermentation but resulting in increased lactic acid production as cells gradually convert sugar to lactic acid after multiplication (Abdullah & Amalia, 2023). Conversely, a high inoculum concentration diminishes cell viability and hinders lactic acid generation (Othman et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…It was indicated that unpeeled banana flour increased the carbohydrate contents of snack bar. For Lactobacillus plantarum banana peel can be used as a carbon source in the fermentation of lactic acid [34].…”
Section: Macronutrients Dietary Fiber and Total Sugar Of Snack Barmentioning
confidence: 99%